Endings: Concluding, Archiving, and Preserving Digital Projects for Long-Term Usability - Carlin, Claire (KULA)

(untitled) (University of Victoria Libraries, 2018)
This report describes some of the practical solutions to the challenges of long-term digital preservation being developed by the project Endings: Concluding, Archiving, and Preserving Digital Projects for Long-Term Usability at the University of Victoria.